ANALISIS PEMASARAN DAN TATANIAGA ANGGUR DI BALI - SUHARYANTO -; IDA AYU PUTU PARWATI; JEMMY RINALDI (Program Studi Agribisnis, Fakultas Pertanian, Universitas Udayana Jalan PB.Sudirman Denpasar, Bali, Indonesia. Telp: (0361) 223544 Email: soca@unud.ac.id, 2008)
Bali grape, especially that effort at Buleleng district is one of local specific commodity thathas great potency to be developed. Marketing aspect is important to support the increasing ofgrape farmer’s income. The number of trading institution that involved to grape marketingwill influence to the length of market chain and the amount of market cost. The amount ofmarket cost will point to the higher difference prices between producer farmer and consumer.For that purpose, analysis of marketing and trading of grape was conducted at Bulelengdistrict. The research location was selected using purposive sampling technique at location of‘Primatani Renovasi’ assessment at Gerokgak sub district, Buleleng. The research was donefrom August to December 2005 using survey method to 50 grape farmers that selectedrandomly and 20 grape traders that selected using snowball sampling technique. Data wasanalyzed descriptively to financial feasibility, market channeling, market margin, marketintegration, and elasticity of price transmission. The result showed that grape farming systemat Gerokgak sub district had well enough prospective. It was indicated by the increasing ofincome per year and BCR value that has tendency to increase year by year. There was 4 grapemarket channeling model at Buleleng, i. e.: Model 1: farmer – commission agent – collectingtrader – retailer – consumer was 14%; Model 2: farmer – collecting trader – retailer –consumer was 44%; Model 3: farmer – collecting trader – district level trader – retailer –consumer was 34%; and Model 4: farmer – retailer – consumer was 8%. The highest marketmargin was gained by Model 1 (3600 rps/kg), followed by Model 3 (3450 rps/kg) and Model2 (3350 rps/kg). While, the highest share accepted by farmer was for Model 3, i. e. 37,89%,followed by Model 2 (33%) and Model 1 (31%). Market integration degree between market atfarmer level and market at consumer level was low, with coefficient value was 0,199. Valueof elasticity of price transmission was 0,457%. Marketing function done by grape marketexecutor included changing function (buying and selling), physically function (transportation,distribution, and storage), facility function (grading and packing); without certification andlabelling.